DEVELOPMENT OF MATHEMATICS SUPPORTER BOOK FOR MI/SD 1 MI/SD BASED ON PEACE EDUCATION - Ulfa, Nanik; Salim, Salim (Study program PGSD FKIP Universitas Bung Hatta, 2022)
Research on the development of teaching materials aims to help educators to facilitate learning activities, namely to provide alternatives for teachers in improving students' abilities and skills in arithmetic. The development of peace education-based teaching materials was carried out in class 1 MI Miftahul Huda Kepanjen. This development research uses the ADDIE model, namely analysis (analysis), design (design), development (development), implementation (implementation), and evaluate (evaluation). The data used in this study are qualitative and quantitative data, with instruments including validation sheets, observation sheets and written test sheets. The research trial was carried out with two kinds of effectiveness tests, namely the material effectiveness test and the effectiveness test of strengthening peace education character education. To test the effectiveness of the material carried out by two tests, namely a small-scale test with 10 students and a large-scale test with 33 students. The validation test on the design expert showed an average of 86 with a valid category, while the material test on the material expert got an average score of 89 with a very valid category. The results of the trial showed an increase in both the mastery of the material and the strengthening of peace education character education. At the end of the material effectiveness test, the average pre-test was 69, and the post-test average was 85, indicating an increase of 23%.